Bagration 1944 the destruction of army group centre - Zaloga, Steve (Praeger illustrated military history series, 2004)
On 22 June 1944, three years to the day after Germany's 1941 invasion of the Soviet Union, the Red Army launched a massive offensive in Byelorussia. Codenamed 'Operation Bagration', this campaign climaxed five weeks later with the Red Army at the gates of Warsaw. The Wehrmacht's Army Group Center was routed, a total of 17 Wehrmacht divisions were utterly destroyed, and over 50 other German divisions were shattered. It was the single most calamitous defeat of the German armed forces in World War II.